Biologicals in rheumatoid arthritis: current and future. Issue 1 (5th August 2015) - Avci, Ali Berkant; Feist, Eugen; Burmester, Gerd-R
Abstract : The aim of the review is to highlight the current knowledge about established and new biologicals and to summarise recent advances by focusing on comparative efficacy, safety and possible discontinuation of treatment in patients with rheumatoid arthritis (RA). Up to now, comparative analyses showed only minor differences with respect to efficacy and safety among the established biologicals. Studies confirmed the excellent drug retention rate as well as efficacy and safety of approved biologicals including their use in monotherapy. Tapering and in some instances discontinuation of biologicals is possible in disease remission. In case of relapse, patients usually show full response after reintroduction of the same compound. The development of biologicals continues fast with several new biologicals targeting different or established cytokines or cellular subsets of the immune system. With several new biologicals in the pipeline and different formulations for established compounds, treatment options for RA will become even more versatile and sophisticated. Although we get closer to the aim of decreasing the proportion of refractory patients, many questions have to be addressed in the near future regarding emerging biosimilars and biologicals with new modes of action.